Synthesis and characterization of the titanium catalysts supported by pyrrolide-benzoxazole ligands and their application in ethylene polymerization. (1st June 2022) - Sun, Ying; Xu, Suting; You, Fen; Shi, Xiaochao
Graphical abstract: The titanium complexes bearing pyrrolide-benzoxazole ligands were synthesized and employed for ethylene polymerization. Up on the activation of MAO, all the titanium complexes 2a -2d and 3a showed moderate activities for ethylene polymerization and produced high-molecular-weight PEs. Abstract: The novel pyrrolide-benzoxazole [NN] titanium complexes TiL2 Cl2 [L = 2-(5-R-benzo-[d]xazol-2-yl)-pyrrole, R = H (2a ), R = CH3 (2b ), R =  t Bu (2c ), R = Cl (2d )] were synthesized. All the complexes were fully characterized by 1 H, 13 C NMR spectra and elemental analyses and the molecular structures of 2b and 2d were determined by single crystal X-ray diffraction. In the presence of methylaluminoxane (MAO), the titanium complexes showed moderate catalytic activities for ethylene polymerization to afford high-molecular-weight polymers.